Dynamic single‐cell analysis of Saccharomyces cerevisiae under process perturbation: comparison of different methods for monitoring the intensity of population heterogeneity. Issue 2 (26th June 2014) - Delvigne, Frank; Baert, Jonathan; Gofflot, Sébastien; Lejeune, Annick; Telek, Samuel; Johanson, Ted; Lantz, Anna Eliasson
Abstract BACKGROUND Single cell biology has attracted a lot of attention in recent years and has led to numerous fundamental results pointing out the heterogeneity of clonal cell populations. In this context, microbial phenotypic heterogeneity under bioprocessing conditions needs to be further investigated. In this study, yeast based processes have been investigated by using on‐line flow cytometry (FC) in combination with a fluorescent transcriptional reporter (GFP) and viability fluorescence tags (propidium iodide, PI). Methods aiming at expressing the dispersion of these fluorescence tags among the yeast populations have been investigated for different bioreactor operating conditions. RESULTS Yeast viability was determined on the basis of PI uptake. Segregation between PI negative and positive subpopulations could be efficiently quantified on the basis of the mean‐to‐median ratio or the amplitude of the interquartile range. On the other hand, the same quantification could not be made for the segregation occurring at the level of GFP synthesis. Indeed, when cells were exposed to sub‐lethal or mild stresses (such as in scale‐down reactors) two GFP subpopulations could be visualized by real‐time FC, but quantification by one of the above‐mentioned methods was not possible. CONCLUSIONS Yeast population heterogeneity was observed in representative bioreactor operating conditions. Difficulties for the determination of segregation at the level of GFP synthesis point out the fact that one needs to understand the segregation mechanisms for the applied fluorescent reporters, to judge whether simple mathematical tools may be applied or if more sophisticated computational tools are needed for quantification of the microbial population segregation. © 2014 Society of Chemical Industry